2011
DOI: 10.1371/journal.pone.0018738
|View full text |Cite|
|
Sign up to set email alerts
|

Biphasic Electrical Currents Stimulation Promotes both Proliferation and Differentiation of Fetal Neural Stem Cells

Abstract: The use of non-chemical methods to differentiate stem cells has attracted researchers from multiple disciplines, including the engineering and the biomedical fields. No doubt, growth factor based methods are still the most dominant of achieving some level of proliferation and differentiation control - however, chemical based methods are still limited by the quality, source, and amount of the utilized reagents. Well-defined non-chemical methods to differentiate stem cells allow stem cell scientists to control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 33 publications
5
88
0
Order By: Relevance
“…The effects of EFs on differentiation are diverse, depending on the target cell and exposure conditions, and it is difficult to directly compare studies that use experimental parameters that differ in many aspects. In a study conducted by Chang et al, biphasic electric currents were found to promote both proliferation and neuronal differentiation of fetal mouse NPCs (Chang et al, 2011). Under control conditions, there was 6.7 times more glial than neuronal differentiation, but this ratio reduced to 3.6-4 in electric stimulation groups after 7 DIV.…”
Section: Discussionmentioning
confidence: 92%
“…The effects of EFs on differentiation are diverse, depending on the target cell and exposure conditions, and it is difficult to directly compare studies that use experimental parameters that differ in many aspects. In a study conducted by Chang et al, biphasic electric currents were found to promote both proliferation and neuronal differentiation of fetal mouse NPCs (Chang et al, 2011). Under control conditions, there was 6.7 times more glial than neuronal differentiation, but this ratio reduced to 3.6-4 in electric stimulation groups after 7 DIV.…”
Section: Discussionmentioning
confidence: 92%
“…ES significantly increases the proliferation and differentiation of fetal neural stem cells into neuronal cells [12], and strongly promotes cell differentiation of human neural stem cells [13] and embryonic stem cells [14]. Furthermore, in vivo studies also revealed that ES promotes the release of neurotrophic factors [15], which maintain survival and proliferation of stem cells after nerve injury and facilitate stem cell differentiation into Schwann Cell-like cells [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…9) and FTIR (Figs. [11][12], and NaCl was detected in the first three hours of immersion in SBF for all samples apart from F-1, as shown in Table 3. The precipitation of halite could be attributed to the high concentration of Na + and Cl − ions in the SBF [61] and/or to the bioactive behaviour of the produced glasses [62].…”
Section: In-vitro Bioactivity In Sbfmentioning
confidence: 81%
“…Also, it has been demonstrated that the presence of yttrium in biomaterials increases their electrical conductivity [10], which could be beneficial for bone regeneration, as cell proliferation has been shown to be sensitive to electrical currents [11]. Although the optimum concentration level of yttrium for promoting osteoblast differentiation and proliferation is still ambiguous, the beneficial aspects of this element have been reported to be dosedependent [12].…”
Section: Introductionmentioning
confidence: 99%